MANAGEMENT OF CHEMOTHERAPY-RESISTANT GASTRIC DIFFUSE LARGE B-CELL LYMPHOMA: A CASE REPORT - Hüseyin Derya Dinçyürek; Müjgan Çözeli; Rashad Abdullayev; Emircan Kiracı; Naciye Nur Tozluklu; Burak Demir; Birol Güvenç (Hematology, Transfusion and Cell Therapy)
Introduction: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma, often affecting extranodal sites like the stomach. While R-CHOP chemotherapy is the standard treatment, some patients fail to respond, requiring alternative approaches. In this report, we describe a case of gastric DLBCL in a 68-year-old man who became resistant to R-CHOP but achieved remission with R-DHAP. Case Report: A 68-year-old man came to the hospital with symptoms of persistent indigestion. After undergoing an endoscopic biopsy in October 2020, he was diagnosed with high-grade gastric diffuse large B-cell lymphoma. A PET-CT scan revealed a large mass in his stomach. He started R-CHOP chemotherapy, completing eight cycles. However, after five cycles, imaging showed remaining disease in the stomach, along with new lesions in the left lung. Despite ongoing treatment, a biopsy after the sixth cycle confirmed that the lymphoma was still active. The situation worsened—his disease had become resistant to R-CHOP. In response, his treatment shifted to R-DHAP chemotherapy. After just two cycles, an endoscopic biopsy revealed no active lymphoma, and only signs of chronic atrophic gastritis remained. PET-CT scans over the following months showed no recurrence of lymphoma. However, in March 2023, a PET-CT showed some hypermetabolic lymph nodes in the cervical region, but these had regressed significantly compared to previous scans. As of October 2024, the patient continues to be closely monitored and remains asymptomatic. Discussion: This case highlights the challenges faced when dealing with chemotherapy-resistant DLBCL. It emphasizes the need to pivot quickly to alternative therapies, like R-DHAP, when first-line treatments fail. The successful response in this patient demonstrates that adjusting treatment strategies can make a significant difference in outcomes. Additionally, it shows the importance of long-term follow-up, especially with extranodal lymphomas, where the risk of relapse is ongoing.